PENINGKATAN KEPUASAN STAKEHOLDER MELALUI IMPLEMENTASI SISTEM PEMBAYARAN VIRTUAL ACCOUNT PADA MADRASAH IBTIDAIYAH KEBONSARI MALANG - Fatiq, Diska Firzan Nadia; Iksan, Mohamad; Prabowo, Sugeng Listyo (Jurnal Manajemen Pendidikan, 2025)
This study investigates the mechanisms for improving stakeholder satisfaction through the implementation of a Virtual Account (VA) payment system in the unique context of the Islamic Elementary School (MI) in Kebonsari, Malang. This study used a qualitative method with a case study approach. Data were collected through triangulation techniques, including in-depth interviews, observation, and document analysis, with a total of eight key informants. The results revealed several findings, including: 1) Transformation of Service Ease and Access: The VA significantly improved perceived ease of use and flexibility for parents, eliminating non-monetary costs such as time and effort in transportation. 2) Internal Efficiency and Staff Focus Reallocation: Automated reconciliation by the VA drastically reduced the risk of human error and eliminated time spent on routine administrative tasks. This triggered a Staff Focus Reallocation Mechanism toward managerial tasks and core educational functions. 3) Mediating transparency with religious trust and legitimacy: In the madrasah context, real-time VA transparency serves as a signal of integrity in the management of sensitive funds, including alms and zakat. These findings indicate that VA mediates the relationship between transparency and the institution's religious legitimacy, which is a source of ultimate satisfaction for management.